Vocational Technology Education Innovation: Building a Generation of Experts in the Digital Age - Rama, Alzet; Ambiyar, Ambiyar; Lapisa, Remon; Verawardina, Unung (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
This article discusses the importance of innovation in vocational technology education as an effort to build a generation of experts who are competent in facing the challenges of the digital era. In the context of rapid technological development, vocational technology education needs to adapt to remain relevant to the demands of modern industry. This article highlights several key aspects of vocational technology education innovation, including curriculum adaptation relevant to industry developments, the application of practical and project-based learning, the utilization of technology in the learning process, collaboration with industry, as well as the development of soft skills. Through this innovative approach, it is expected that vocational technology education is able to produce graduates who not only have strong technical skills, but are also able to adapt, innovate, and contribute significantly in the ever-evolving world of work. With a focus on building a generation of experts in the digital era, this article.